2022
DOI: 10.1002/pon.5921
|View full text |Cite
|
Sign up to set email alerts
|

What is the prevalence of fear of cancer recurrence in cancer survivors and patients? A systematic review and individual participant data meta‐analysis

Abstract: Objective Care for fear of cancer recurrence (FCR) is considered the most common unmet need among cancer survivors. Yet the prevalence of FCR and predisposing factors remain inconclusive. To support targeted care, we provide a comprehensive overview of the prevalence and severity of FCR among cancer survivors and patients, as measured using the short form of the validated Fear of Cancer Recurrence Inventory (FCRI‐SF). We also report on associations between FCR and clinical and demographic characteristics. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
111
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 98 publications
4
111
1
1
Order By: Relevance
“…There is extensive literature reporting the psychosocial consequences of cancer in curative and end-of-life settings [ 1 , 2 , 3 , 4 ]. However, studies examining the psychosocial outcomes of living long term with advanced cancer in patients receiving ongoing systemic treatment and/or follow-up are scarce [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive literature reporting the psychosocial consequences of cancer in curative and end-of-life settings [ 1 , 2 , 3 , 4 ]. However, studies examining the psychosocial outcomes of living long term with advanced cancer in patients receiving ongoing systemic treatment and/or follow-up are scarce [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 The overall prevalence for FCR is unknown and groups have estimated wide ranges from 39% to 97%. 7 Meta-analyses have found that FCR was found most in women and younger patients, but that FCR occurs in all continents and at all time points since diagnosis. 7 With the improvement in many cancer therapies and subsequently improved patient survival, research into FCR has also grown.…”
Section: Introductionmentioning
confidence: 99%
“…7 Meta-analyses have found that FCR was found most in women and younger patients, but that FCR occurs in all continents and at all time points since diagnosis. 7 With the improvement in many cancer therapies and subsequently improved patient survival, research into FCR has also grown. The modern definition of FCR has evolved and additions include hypervigilance and sensitivity to bodily symptoms that some cancer survivors can develop.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations